2015
DOI: 10.1007/s11064-015-1624-z
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Rescued the Impairments of Primary Hippocampal Neurons Induced by BV2 Microglial Over-Activation

Abstract: Activated microglia plays an important role in monitoring the microenvironment and prune neural process in healthy neural tissue, in order to maintain synaptic homeostasis. However, hyperactive microglia may release various cytotoxic factors and induce neuroinflammation, which cause neuronal damages leading to neurodegenerative diseases. Tanshinone IIA (TSA), an extract from traditional Chinese medicine, features potent anti-apoptotic and anti-inflammatory effects both in vitro and in vivo. But little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…Here, we used a motor neuron-like NSC-34 cell line induced by LPS to mimic the in vitro SCI cell model [ 21 ]. Our results validated that TSIIA protected NSC-34 cells against LPS-induced cell damage, in line with recent work [ 22 , 23 ]. Importantly, we provided a novel molecular explanation for the protective role of TSIIA in LPS-evoked cytotoxicity in NSC-34 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we used a motor neuron-like NSC-34 cell line induced by LPS to mimic the in vitro SCI cell model [ 21 ]. Our results validated that TSIIA protected NSC-34 cells against LPS-induced cell damage, in line with recent work [ 22 , 23 ]. Importantly, we provided a novel molecular explanation for the protective role of TSIIA in LPS-evoked cytotoxicity in NSC-34 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Sole albendazole treatment and albendazole combined with dexamethasone treatment increased the ganglion cell number slightly, whereas CPT or TSII-A combined with albendazole treatment were shown to help almost regain the initial number of ganglion cells, and the latter was more effective, indicating that albendazole combined with TSII-A can rescue the loss of ganglion cells caused by A. cantonensis infection significantly. Previous studies showed TSII-A played a vital role in protecting neurons such as dopaminergic neurons and hippocampal neurons [ 19 , 20 ], and may inhibit thebeta-amyloid-induced toxicity in rat cortical neurons [ 21 , 22 ]. In addition, TSII-A also has a protective effect on the cranial nerves when administered during the initial stages of cerebral ischemia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Activated microglia is of great significance to monitor the microenvironment, clean up the damaged nerves, and prune neural process in healthy central nervous system so as to maintain synaptic homeostasis. 2 However, the continuously over-activated or out of control microglia may induce the release of many cytotoxic factors and lead to some inflammations, which can worsen neuronal damages, thereby resulting in neurodegenerative diseases. 3 Microglia cells are found to be activated and proliferated locally in the pathological process of central nervous system injury, inflammation, depression, Alzheimer's disease, and even epilepsy.…”
Section: Introductionmentioning
confidence: 99%